PENGEMBANGAN OBYEK WISATA BERBASIS COMMUNITY BASED TOURISM (CBT) DI HUTAN PAYAU, CILACAP - Susanto, Dwiyono Rudi; Syaifulloh, Muhammad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2018)
Payau Forest is one of the potential areas of tourism in Cilacap Regency. This is because the natural beauty of the Payau Forest and supported by trend of tourism that leads to nature tourism with attention to the sustainability. The management of the Payau Forest is done by the local community who are members of the community, namely Pokdarwis Maspayau and LMDH (Lembaga Desa Desa Hutan). The purpose of this research is to know (1) the development of Community-Based Tourism object (CBT) in Payau Forest Cilacap and (2) how the local community role in the management and development of tourism Payau Forest of Cilacap. The research method used is qualitative method. Primary data collection is done by interview, observation and literature study. The results of the research shows that the management of Payau Forest tourism in Cilacap implemented through the management of tourism resources, management of tourism marketing, human resource management, and crisis management. By implementing Community Based Tourism (CBT) in the management of Payau Forest can be seen from the active participation of the community in every tourism activity and the nature and cultural preservation. In addition, it is concluded that the level of community participation in the environment of Payau Forest is at the level of citizen control, meaning that people become controllers in the planning, implementation, monitoring and evaluation process in tourism management. Keywords: Community Based Tourism, CBT, Payau Forest, nature tourism, citizen control